Advances in Pharmacokinetic Mechanisms of Transporter-Mediated Herb-Drug Interactions - Jie Li; Shuting Wang; Fengjie Tian; Shuang-Qing Zhang; Hongtao Jin (MDPI AG, 2022)
As the use of herbs has become more popular worldwide, there are increasing reports of herb-drug interactions (HDIs) following the combination of herbs and drugs. The active components of herbs are complex and have a variety of pharmacological activities, which inevitably affect changes in the pharmacokinetics of chemical drugs in vivo. The absorption, distribution, metabolism, and excretion of drugs in vivo are closely related to the expression of drug transporters. When the active components of herbs inhibit or induce the expression of transporters, this can cause changes in substrate pharmacokinetics, resulting in changes in the efficacy and toxicity of drugs. In this article, the tissue distribution and physiological functions of drug transporters are summarized through literature retrieval, and the effects of herbs on drug transporters and the possible mechanism of HDIs are analyzed and discussed in order to provide ideas and a reference for further guiding of safe clinical drug use.